Student Engagement Practices as a Driver of Skill Enhancement in Community-Centric Higher Education - Sharma, Anshul; Dixit, Shailja; Singh, Surabhi; Chandra, Ashish; Tripathi, Rashmi; Durgvanshi, Rashika; Mishra, Manish (International Review of Management and Marketing, 2025)
This study investigates the impact of student engagement practices on skill enhancement in community-centric higher education, with motivation examined as a mediating variable. Engagement is conceptualized as a multidimensional construct, including behavioural, emotional, cognitive, and experiential components, along with faculty support and peer collaboration. Data were collected from 500 students across five cities in Uttar Pradesh, India, using a structured questionnaire. Structural Equation Modeling (SEM) was employed to analyze the proposed relationships. The analysis revealed that all engagement dimensions significantly influence motivation, which in turn strongly predicts skill enhancement in students. Experiential learning and peer collaboration showed the highest direct and indirect effects on engagement. Motivation emerged as a key mediator, linking engagement to outcomes such as improved communication, leadership, and critical thinking skills. The model demonstrated strong reliability, validity, and predictive accuracy. The study offers practical implications for curriculum development, faculty training, and institutional policy by emphasizing the value of active, collaborative, and community-based learning practices. Limitations include the regional sample and cross-sectional design, indicating the need for future research using longitudinal and mixed-method approaches across broader contexts.